Cover Picture: Encapsulation of Heteropolyanion‐Based Ionic Liquid within the Metal–Organic Framework MIL‐100(Fe) for Biodiesel Production (ChemCatChem 3/2015). Issue 3 (February 2015) - Wan, Hui; Chen, Chong; Wu, Zuowang; Que, Yigen; Feng, Yu; Wang, Wei; Wang, Lei; Guan, Guofeng; Liu, Xiaoqin
<x xml:space="preserve">Abstract</x> The cover picture shows how a polyoxometalate (POM) can bridge the gap between ionic liquid (IL) and carrier, thus, the heteropolyanion‐based ionic liquid can be encapsulated within the cages of a metalorganic framework (MOF) through anion exchange to form a composite. In their Full Paper, H. Wan et al. describe their strategy to construct their composite, which showed good catalytic activity for esterification and was stable for liquid‐phase reactions with no obvious leaching of the active component. The article highlighted by this cover can be found on p. ff. of Issue 3, 2015.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>